The deep end - Kinney, Jeff (London Puffin Books, 2022, 2022)
In The Deep End, Book 15 Of The Diary Of A Wimpy Kid Series From #1 International Bestselling Author Jeff Kinney, Greg Heffley And His Family Hit The Road For A Cross-Country Camping Trip, Ready For The Adventure Of A Lifetime. But Things Take An Unexpected Turn, And They Find Themselves Stranded At A Campsite That's Not Exactly A Summertime Paradise. When The Skies Open Up And The Water Starts To Rise, The Heffleys Wonder If They Can Save Their Vacation - Or If They're Already In Too Deep
Greg Heffley and his family hit the road for a cross-country camping trip, ready for the adventure of a lifetime. But things take an unexpected turn, and they find themselves stranded at an RV park that's not exactly a summertime paradise. When the skies open up and the water starts to rise, the Heffleys wonder if they can save their vacation-or if they're already in too deep
English Stories
For children aged 11 - 15 years
1 2 23
Keywords: Heffley, Greg -- Juvenile fiction; Family vacations -- Juvenile fiction; Recreational vehicle camping -- Juvenile fiction